The protection of employees in the early warning tools and preventive restructuring frameworks: the EU Directive 2019/1023 (“Insolvency Directive”) and the Italian Crisis and Insolvency Code (Legislative Decree no. 14/2019) - Andrea Pilati (Italian Labour Law e-Journal, 2025)
The contribution focuses on recent legislative developments at both European and Italian level concerning corporate crisis (UE Insolvency Directive and Italian Code of business crisis and insolvency). It explores the issues that most directly affect employees involved in negotiated crisis resolution procedures and in preventive restructuring frameworks. The paper highlights the provisions that ensure a more effective protection of employees’ rights compared to those of other creditors. It also offers some critical reflections on the issue of information and consultation rights of workers’ representatives, which have not achieved significant progress under the Italian Code of Business Crisis and Insolvency.